Congenital Megaprepuce: Literature Review and Surgical Correction - Zachary Werner; Ali Hajiran; Osama Al-Omar (Case Reports in Urology)
Congenital megaprepuce (CMP) is a type of buried penis characterized by extensive redundancy and ballooning of the inner prepuce as a result of preputial stenosis and phimosis. The malformation typically presents with difficulty voiding, often requiring manual expression of stagnant urine. Multiple techniques have been reported for the treatment of CMP with varying levels of positive outcomes. The authors provide a review of published literature, in addition to describing the procedure and results of our surgical technique in three children aged eleven months, two years, and twelve years. The literature review was conducted using PubMed with keywords “congenital megaprepuce,” “megaprepuce,” “buried penis,” “CMP,” and “correction.” Results were then differentiated based on presence or absence of true congenital megaprepuce and the surgical correction thereof. Regarding our cases, all patients completed the procedure with excellent cosmesis and without complication. Our technique is shown to provide consistent, excellent esthetic outcome across a wide range of ages and may be replicated by others.